Global aromaticity in a partially fused 8-porphyrin nanoring - Kopp, SM; Gotfredsen, H; Deng, J-R; Claridge, TDW; Anderson, HL (American Chemical Society, 2020)
Template-directed synthesis has been used to prepare a fully π-conjugated cyclic porphyrin octamer, composed of both β,meso,β-edge-fused porphyrin tape units and butadiyne-linked porphyrins. The UV–vis–NIR spectra of this partially fused nanoring show that π-conjugation extends around the whole macrocycle, and that it has a smaller HOMO–LUMO gap than its all-butadiyne-linked analogue, as predicted by TD-DFT calculations. The 1H NMR shifts of the bound templates confirm the disrupted aromaticity of the edge-fused porphyrins in the neutral nanoring. NMR oxidation titrations reveal the presence of a global paratropic ring current in its 4+ and 8+ oxidation states and of a global diatropic ring current in the 6+ state of the partially fused ring. The paratropic ring current in the 4+ oxidation state is about four times stronger than that in the all-butadiyne-linked cyclic octamer complex, whereas the diatropic current in the 6+ state is about 40% weaker. Two isomeric K-shaped tetrapyridyl templates with trifluoromethyl substituents at different positions were used to probe the distribution of the ring current in the 4+, 6+, and 8+ oxidation states by 19F NMR, demonstrating that the ring currents are global and homogeneous.